A Five Years Review Intra-Operative Cholangiogram - Shah, J N; Shah, C (Journal of Nepal Health Research Council, 2011)
Background: Intra-operative cholangiogram is often performed to detect concurrent common bile duct stones in cholecystectomy patients. Routine cholangiogram add to cost and exposes patients to unnecessary exploration of common bile duct due to frequent false positive results. Thus, there is need of better indicators for cholangiogram in order to minimize unnecessary procedure and its morbidity. Methods: A retrospective analysis of patients undergoing intra-operative cholangiogram during open or laparoscopic cholecystectomy was done at Patan Hospital from Oct 1, 2005 to Sep 31, 2009. Indications and outcome of cholangiogram were analyzed together with findings of common bile duct exploration. Results: A total of 68 (2.8%, 68/2400) intra-operative cholangiogram were done in 2400 cholecystectomy patients during five years period. Eight (11.8%, 8/68) patients had abnormal findings. Two (3%, 2/68) patients with abnormal cholangiogram had stones in common bile duct. There was no mortality in this series. Conclusions: Existing indications of intra-operative cholangiogram detects only small percentage of patients with bile duct stones and has high false positive results. This unnecessarily increases bile duct exploration, cost and morbidity. Thus, there is need to redefine indications for intra-operative cholangiogram. Keywords: biliary pancreatitis, cholecystectomy, common bile duct, intra-operative cholangiogram.